The economic legacy of civil war: Firm level evidence from Sierra Leone - Paul Collier; Marguerite Duponchel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper positions itself among the very rare microeconomic analyses on the consequences of civil war. Up to now, most analyses on this topic are based upon household surveys. The originality of the present study is that it investigates for the first time the likely predominant route by which civil conflict affects the economy, namely through firms. The context of the study is Sierra Leone, a country that was ravaged by a violent conflict from 1991 to 2002. The approach is to use geographical variations in the intensity of conflict to estimate the impact of violence on firms, on which we have data from the World Bank 2007 Employers Survey. The proposed theory is that during the conflict, violence affects production through a form of technical regress and demand through a reduction in income. The persistent post-conflict effects are yet less obvious We assume that war forces a prolonged contraction in output skills, which slows the pace of recovery. We termed this phenomenon 'forgetting by not doing'. The results confirm our theory. Civil war negatively impacts the existence of firms and employment, but there is no distinction between regions. However, the size of firms in 2006 is negatively affected by the intensity of the war in the area it operates. Yet, firms tend to grow twice faster in more affected areas, strikingly matching the macroeconomic rate of recovery post-conflict environments (Collier and Hoeffler, 2004). The analysis of training patterns clearly confirms the long lasting lack of skills experienced as a result of the war in areas where the conflict was more intense.
Keywords: O01; O33; L26; 330; entrepreneurship; national systems of innovation; SMEs; innovative; capabilities; emerging economies